Women doing platform work – opportunities, challenges and career prospects - Bednarz, Wiktoria (Problem zakresu regulacji ustawowej nietypowych form zarobkowania na przykładzie zatrudnienia zewnętrznego i pracy platformowej, 2025)
The dynamic development of platform work, although it creates many new professional opportunities for women, also poses many challenges. The aim of this article is to analyse the potential of this form of work in terms of its impact on women’s professional development – while taking into account the opportunities and existing difficulties. Platform work, by means of its multifaceted flexibility, makes it possible to adapt the time and place of work and the number of tasks to be performed, but the lack of adequate protection of numerous labour rights poses a major challenge for many actors. The article highlights the need for legislation (notably the implementation of Directive (EU) 2024/2831 of the European Parliament and of the Council of 23 October 2024 on the improvement of working conditions through platforms) that could improve working conditions through digital platforms and guarantee equality for all its workers.